La sociolinguistique au secours des juristes - Tousignant, Claude (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1991)
Over the past twenty or so years, more and more linguists have been called upon to give evidence in U.S. and Canadian Courts. The fields in which they have provided testimony include that of socidinguistic analysis based on the link-up between language and society. The evidence they provide of the testimony between the socio-economic background of an accused person and his or her linguistic production may, for example, determine the validity of a confession or the justification for a libellous statement attributed to the accused. However, the lawyer who is familiar with and can master the various social connotations associated with the various expressions used in court will have a major advantage when it comes to encouraging a witness to speak out, or convincing the judge and jury of the credibility of what he or she tells them.